2013
DOI: 10.1371/journal.pone.0055582
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Machine Learning Methodologies to Analyse Antibiotic and Biocide Susceptibility in Staphylococcus aureus

Abstract: BackgroundThe rise of antibiotic resistance in pathogenic bacteria is a significant problem for the treatment of infectious diseases. Resistance is usually selected by the antibiotic itself; however, biocides might also co-select for resistance to antibiotics. Although resistance to biocides is poorly defined, different in vitro studies have shown that mutants presenting low susceptibility to biocides also have reduced susceptibility to antibiotics. However, studies with natural bacterial isolates are more lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
2
29
1
Order By: Relevance
“…Similar chlorhexidine MICs (0.5 to 1 mg/liter) were found in MRSA and MSSA populations (85.0% [70/82 isolates] of MRSA versus 91.8% [201/219 isolates] of MSSA; P ϭ 0.1285), as previously reported for MRSA isolates from human and animal origins (10,31). To date, there is no breakpoint consensus to define biocide-reduced susceptibility, and independent reports have proposed different epidemiological cutoff (ECOFF) values based on the normal distribution of MICs in different S. aureus populations (27,32,33). In our study, an MIC cutoff of Ն1 mg/liter was defined, since Ͻ1% of the isolates showed an MIC of Ն2 mg/liter.…”
supporting
confidence: 56%
“…Similar chlorhexidine MICs (0.5 to 1 mg/liter) were found in MRSA and MSSA populations (85.0% [70/82 isolates] of MRSA versus 91.8% [201/219 isolates] of MSSA; P ϭ 0.1285), as previously reported for MRSA isolates from human and animal origins (10,31). To date, there is no breakpoint consensus to define biocide-reduced susceptibility, and independent reports have proposed different epidemiological cutoff (ECOFF) values based on the normal distribution of MICs in different S. aureus populations (27,32,33). In our study, an MIC cutoff of Ն1 mg/liter was defined, since Ͻ1% of the isolates showed an MIC of Ն2 mg/liter.…”
supporting
confidence: 56%
“…In one of the largest phenotypic studies ever performed on biocides and on AMR, a total of 1632 worldwide clinical strains of S. aureus were analyzed …”
Section: Machine Learning To Predict Amrmentioning
confidence: 99%
“…In one of the largest phenotypic studies ever performed on biocides and on AMR, a total of 1632 worldwide clinical strains of S. aureus were analyzed. 67 S. aureus is a major human pathogen, a major cause of nosocomial infections, and a significant cause of foodborne infection. By combining different machine learning methodologies, namely decision trees and clustering, to explore the data in order to find biologically and statistically significant results, it was demonstrated that reduced susceptibility to two common biocides, chlorhexidine and benzalkonium chloride, which belong to different structural families, is associated with multi-AMR.…”
Section: Machine Learning To Predict Amrmentioning
confidence: 99%
“…For this scope, we performed a comparative molecular and phenotypic characterization of the susceptibility to benzalkonium chloride and chlorhexidine (CHX) in the clinically relevant model organism S. aureus. This work is part of the multicenter BIOHYPO project, which aims to evaluate the impact of biocide use in the food chain on antimicrobial drug resistance of clinical relevance in enterobacteria, Gramnegative nonfermenters, staphylococci, enterococci, lactic acid bacteria, and fungi (2,(22)(23)(24)(25)(26)(27). In this context, the detailed characterization of biocide susceptibility phenotypes and genotypes is the first step of correlation of these data with antimicrobial resistance profiles.…”
mentioning
confidence: 99%